Analisis Penyusunan Anggaran Bantuan Operasional PAUD Nur Permata Hijau Kabupaten Banggai - Nur Atni Botutihe; Miftahul Ilmi (Journal of Technopreneurship on Economics and Business Review, 2021)
The purpose of this study was to determine the budgeting of operational assistance fund the Early Childhood Education (PAUD) Nur Permata Hijau in Lumpoknyo Village, Banggai Regency. The data analysis method used in this research is a qualitative descriptive analysis technique to thoroughly describe the implementation of BOP budgeting reporting in PAUD Nur Permata Hijau and is associated with public sector accounting, especially in public sector budgeting. The results showed that the preparation of the budget for school operational funds at PAUD Nur Pemmata Hijau in 2019 was in accordance with the Regulation of the Minister of Education and Culture Number 4 of 2019. The preparation of the operational budget for PAUD Nur Permata Hijau was effective and efficient because the budget was absorbed in its entirety and the use of the budget was already very appropriate for student activities.